Annotated Catalogue of the Genus Diplodon (Unionacea - Hyriidae) - J. J. Parodiz (Hello World!, 1968)
The present cataIogue lists alI specific and subspecific names introduced since 1792 into the generic group now known as Diplodon Spix 1827. Names in capitals are followed by the original reference of the taxon and type locality. References have been kept to a minimum in order to simplify the procedure; for authors as d'Orbigny Lea, and Simpson, who first diagnosed their species briefly without giving illustrations, the next reference with full description and figures is added. Lea usually reprinted his own description in several journals, but the original reference is followed by that of the 'Observations on the genus Unio,' which ran for 13 volumes and compiled all his descriptions and figures.